Lexical Analysis on Writing Interference of Medical Students - Muhammad Rudy; Diah Kristina; Sri Samiati Tarjana (Journal of English Language Studies, 2018)
One of the impacts that can be observed on language differences during learning English is interference. Indonesian medical students have problem with writing; what they said did not reflect what they meant to. This descriptive analysis study identified the interference on medical students while doing writing activity in the class. Four students were chosen randomly as the subjects to give their written diagnosis. The analysis was done on basis of lexical interference after categorizing formal error on their writing. The result showed that error distributions were omissions, coinage, claque, misselection, borrowing, misordering and overinclusion, where the most prominent was omission. This problem may happen due to first language, language learning process and the English words themselves. The strategy of writing instruction can be started from vocabulary understanding to minimize writing errors.